Vaginoplasty with Acellular Dermal Matrix after Radical Resection for Carcinoma of the Uterine Cervix - Zhi Wang; Jiuzuo Huang; Ang Zeng; Ming Wu; Xiaojun Wang (Journal of Investigative Surgery, 2019)
Various methods are available for vaginoplasty, but many of them have the drawbacks including surgical complexity and postoperative pain at the donor site. We herein evaluated the outcomes of vaginoplasty using tissue-engineered biomaterial graft. This study included 16 early stage cervical cancer patients who received curative surgery in combination with radiotherapy. They underwent vaginoplasty with tissue-engineered biological material, acellular dermal matrix (ADM). After treatment, a vaginal dilator was advised to be used for 6 months to prevent contraction of vagina. The effectiveness of the treatment was evaluated by the anatomic changes of vagina before and after treatment, and the sexual outcomes at 12-month after treatment. The procedure was safe with no intra-operative complications reported. The mean operation time was 1.7 ± 0.3 hours, with 11/16 patients had blood loss < 50 mL during surgery. Generally, epithelialization was observed in 2-week after treatment. At the 1-year follow-up visit, the mean vaginal width was increased significantly from 1.31 ± 0.4 cm before surgery to 4.13 ± 0.43 cm after surgery (p = 0.034). The vaginal length was also increased from 5.97 ± 0.59 cm to 9.25 ± 0.66 cm (p < 0.001). Majority of the patients (12/16) reported satisfactory sexual life. The use of ADM in vaginoplasty was a safe and effective procedure that provided satisfactory sexual function for patients with vaginal abnormalities after cervical cancer treatment.